Factors Influencing Purchasing Intention of Smartphones among UTHM Students - Rashid, Umi Kartini; Nasuredin, Juzaimi; Omar, Siti Sarah; Ismail, Fadillah (Research in Management of Technology and Business, 2020)
Smartphone has dramatically become a part of lifestyle for the people around the world. Despite the pervasiveness of smartphone penetration in Malaysia, studies that have been conducted to understand the consumers’ preferences on a smartphone, especially for young adults are still lacking. Therefore, this study attempted to examine the factors that influenced the purchase intention of smartphones among UTHM students, namely product features, brand name, product price and social influence. A total of 375 structured questionnaires were distributed among undergraduate students in UTHM using probability sampling technique and data was analysed using SPSS. The results revealed that all four factors had significant relationships with the purchase intention. This study is important for the marketers to understand the consumers’ behaviour and to be more competitive towards their target segmentation’s smartphone purchase decision. However, in consideration with the limitation of population and sampling size, future researchers are suggested to conduct the similar study in a bigger population such as comparing among the different states in Malaysia for more rigorous findings and to be able to generalize in a bigger context.